Logistics Development and Local Supports: A Case of Pak Bara Port in Thailand - Pimpika Chawalit; Benjenop Buranasiri; Pairach Piboonrungroj (International Journal of Supply Chain Management, 2016)
Governments usually use Logistics development to drive economic and trade development at the national and international stage. However, in various cases there are some negative impacts incur from such project in the development area. Such conflict has been discussed widely but seldom in academia. To understand the underlying reason for such conflict, this study aims to develop and examine the logistics on resident supports in the deep-sea port project. We test the model with the case of Pak Bara Deep Sea port on the West Coast of Thailand according the on-going attempt of the government for the project but lacks of supports from the local community. A research model was developed under the concept sustainable development and related studies on logistics impacts and social supports. The model was empirically tested using the Structural Equation Model (SEM) technique to explain the endogenous latent variable (support for the Pak Bara deep-sea port) and logistics impact as one of the exogenous latent variables together with economics, environment, social and culture, technology, and trust). Survey data were collected using self-administrative questionnaires from 310 residents in Satun province, where the project located. The study found that perceived impacts on environment, logistics, and trust in government significantly affect the resident supports. The path analysis shows that logistics aspect affects the resident supports the most. Moreover, the path analysis of each item shows that satisfying in transportation affects the resident supports the most. Contrast to many believe, It was also found that logistics impacts is critical to local residents as well as social impacts, whilst economic and environmental impact are more concerned by outsiders.